1994
DOI: 10.1165/ajrcmb.10.6.8003340
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of lung branching morphogenesis by bombesin-like peptides and neutral endopeptidase.

Abstract: The expression of bombesin-like peptides (BLPs) by pulmonary neuroendocrine cells is transiently upregulated during lung development. A functional role for BLPs is supported by their ability to stimulate lung growth and maturation both in vitro and in vivo during the late stages of lung development. In addition, the cell membrane-associated enzyme CD10/neutral endopeptidase 24.11 (CD10/NEP), which inactivates BLPs and other regulatory peptides, is also expressed by developing lungs and modulates the stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…In the mouse, Sunday et al and King et al (28,29) have demonstrated that bombesin can stimulate DNA and saturated phosphatidylcholine (SPC) synthesis in fetal lung. Similarly, Aguayo et al (30) have also demonstrated that bombesin can stimulate airway branching in mouse lung explants. However, it is noteworthy that the GRP is expressed relatively later in gestation in mice than in humans (17,28), and that in contrast to humans, GRP immunoreactivity cannot be localized to mouse PNEC (31 ).…”
mentioning
confidence: 81%
“…In the mouse, Sunday et al and King et al (28,29) have demonstrated that bombesin can stimulate DNA and saturated phosphatidylcholine (SPC) synthesis in fetal lung. Similarly, Aguayo et al (30) have also demonstrated that bombesin can stimulate airway branching in mouse lung explants. However, it is noteworthy that the GRP is expressed relatively later in gestation in mice than in humans (17,28), and that in contrast to humans, GRP immunoreactivity cannot be localized to mouse PNEC (31 ).…”
mentioning
confidence: 81%
“…The murine lung explant model has been previously described (1). Briefly, timed pregnant CD57BL/6J mice were killed to obtain embryos at embryonic day 11(E11).…”
Section: Animalsmentioning
confidence: 99%
“…Its encoding gene is on chromosome 3, and it has a molecular weight of 98,000, is characterized by a neutral optimum pH, and is a plasma membrane-bound metalloproteinase (17). Many peptides have been found to be substrates for NEP, for example, enkephalin (20,21), substance P (22), bombesinlike peptide (16,23), endothelin (24,25), bradykinin (22) and others (26). The other name for NEP, enkephalinase, reflects the fact that NEP can degrade enkephalin in association with nerves (21,27,28).…”
Section: Discussionmentioning
confidence: 99%